(untitled) - Jon Peckma; Jon Peckma (Boston, MA, 2007)
Imagine yourself onstage with your band. As the band plays, the crowd moves to the rhythm-your rhythm. The rhythm that you feel in your bones and set loose on the crowd. Drummers aren't front and center. They're not often the face of the band. Instead, they are its heart. It's the drummer who sets the pace and keeps the song on track. Picture Yourself Drumming is an easy-to-follow, visual guide that will help you tackle the basic skills you need to someday control that crowd with your own driving beat. If you have some natural rhythm, a set of sticks, and a desire to become a drummer, then this book was written for you. The accompanying DVD includes tips for a variety of drumming techniques as well as coaching sessions and step-by-step instructions for setting up each piece of your new drum kit
Keywords: Drum --Instruction and study; Drum set --Instruction and study; Drum --Methods --Self-instruction